Per-Contact Infectivity of Hepatitis C Virus Acquisition in Association With Receptive Needle Sharing Exposures in a Prospective Cohort of Young Adult People who Inject Drugs in San Francisco, California. (16th March 2020) - Leyva, Yuridia; Page, Kimberly; Shiboski, Stephen; Hahn, Judith A; Evans, Jennifer; Erhardt, Erik
Abstract: Background: Sharing needles and ancillary injecting equipment is a primary risk exposure for hepatitis C virus (HCV) infection among people who inject drugs (PWID); however, infectivity of these exposures is not well quantified. We aimed to estimate per-event HCV infectivity associated with receptive needle sharing (RNS) among susceptible PWID. Methods: Participants in a prospective cohort study of young adult PWID who were anti-HCV and HCV RNA negative at baseline and attended at least 2 follow-up study visits between 2003 and 2014 were eligible. Data were selected from the first HCV-negative through the first HCV-positive visit (or last HCV-negative among those uninfected). Anti-HCV and HCV-RNA tests were used to determine infection status. A probabilistic exposure model linking observed HCV infection outcomes to self-reported exposure events was applied to estimate infectivity. Results: Among 344 participants, a maximum likelihood estimate considering RNS yielded a pooled population per RNS event HCV probability of 0.25% (95% confidence interval [CI], 0.10%–0.43%), and 1.12% (95% CI, 0.48%–2.35%) among those who acquired any HCV infection (primary or reinfection). Conclusions: HCV is highly infectious in association with RNS, a primary injection-related risk exposure. Our infectivity estimate among participants who acquired any HCV infection is 1.7 times higher than that estimated for HIV infection in PWID and 2.24 times higher than that estimated among health care workers exposed through needle sticks. The strengths of this study include the assessment of receptive needle sharing events, the prospective design, and relatively short recall and testing periods. These results can inform transmission models and research to prevent HCV infection.